The role of the glycocalyx in reorganization of the actin cytoskeleton under fluid shear stress: A “bumper-car” model - Thi, Mia M. (National Academy of Sciences, 2004)
We propose a conceptual model for the cytoskeletal organization of endothelial cells (ECs) based on a major dichotomy in structure and function at basal and apical aspects of the cells. Intracellular distributions of filamentous actin (F-actin), vinculin, paxillin, ZO-1, and Cx43 were analyzed from confocal micrographs of rat fat-pad ECs after 5 h of shear stress. With intact glycocalyx, there was severe disruption of the dense peripheral actin bands (DPABs) and migration of vinculin to cell borders under a uniform shear stress (10.5 dyne/cm(2); 1 dyne = 10 μN). This behavior was augmented in corner flow regions of the flow chamber where high shear stress gradients were present. In striking contrast, no such reorganization was observed if the glycocalyx was compromised. These results are explained in terms of a “bumper-car” model, in which the actin cortical web and DPAB are only loosely connected to basal attachment sites, allowing for two distinct cellular signaling pathways in response to fluid shear stress, one transmitted by glycocalyx core proteins as a torque that acts on the actin cortical web (ACW) and DPAB, and the other emanating from focal adhesions and stress fibers at the basal and apical membranes of the cell.